2013
DOI: 10.1088/2040-8978/16/1/015203
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast single-shot imaging of femtosecond pulse propagation in transparent liquids using a supercontinuum and optical polarigraphy

Abstract: We investigated the ultrafast time-resolved single-shot imaging of femtosecond pulse propagation using a supercontinuum and optical polarigraphy in transparent liquids. The probe supercontinuum senses the instantaneous birefringence induced by the laser pulse, and a polarigraphy image with different color distributions could be obtained. By comparing the wavelength distributions and the saturation variation of the images, the recorded polarigraphy images in two samples with different response time were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In general, the single-shot pump-probe technique encodes the time delay into a single probe pulse using spatial or spectral strategies. Currently, the commonly used encoding strategies include the angle beam encoding strategy [1,2,[6][7][8], spectral encoding strategy [9][10][11][12], and echelon encoding strategy [3,5,[13][14][15][16]. The angle beam encoding strategy utilizes the crossed line focus of the pump beam and probe beam on the sample plane, and the time delay is encoded along the focal line.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the single-shot pump-probe technique encodes the time delay into a single probe pulse using spatial or spectral strategies. Currently, the commonly used encoding strategies include the angle beam encoding strategy [1,2,[6][7][8], spectral encoding strategy [9][10][11][12], and echelon encoding strategy [3,5,[13][14][15][16]. The angle beam encoding strategy utilizes the crossed line focus of the pump beam and probe beam on the sample plane, and the time delay is encoded along the focal line.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, J 0 and J 1 are the first kind of Bessel functions of order zero and order one, respectively. By Fourier transformation, the total electric field of the ultrashort light pulse near the focus can be obtained by superposition of each spectral component as [21]:…”
Section: Theoretical Analysismentioning
confidence: 99%
“…Study of double-ring-shaped radially polarized light beams in tight focusing has shown that near the focus of the high-NA objective, the longitudinal component varied with the degree of truncation of the incident beam by the pupil of the objective lens because of the interference between the longitudinal components of the inner and outer rings [18]. Meanwhile, ultrashort light pulses that have temporal resolution down to the femtosecond range have recently been used in several time-resolved optical measurements [10,[19][20][21]. In optical measurements with a femtosecond light pulse, the spatial and temporal properties of the focused ultrashort light pulse may influence the resolution of a produced image [22].…”
Section: Introductionmentioning
confidence: 99%